How Do Groundwater Levels and Soil Moisture Influence the Peat Fire Vulnerability Index in Oil Palm Plantations? - Purnamayani, Rima; Tarigan , Suria Darma; Sudradjat, Sudradjat; Syahbuddin, Haris; Dariah, Ai; Kartiwa, Budi (Journal of Tropical Crop Science, 2025)
Peatland fires are a significant environmental issue, impacting local ecosystems and contributing to global climate change. This study evaluates the Peat Fire Vulnerability Index (PFVI) for sapric and hemic maturity levels under oil palm plantations in Pangkalan Pisang Village, Riau Province. Data on groundwater level, soil moisture, rainfall, and maximum temperature were collected from December 2021 to December 2022. The PFVI, modified from the Keetch-Byram Drought Index (KBDI), was calculated and correlated with these variables. The groundwater level varied from 3 cm to 76 cm below the surface, with an average of 36.23 cm. In sapric blocks, 29% of the groundwater level was less than 40 cm, while 73% were deeper. In hemic blocks, 44% were less than 40 cm, and 56% were deeper. Soil moisture in the top 10 cm layer fluctuated between 32% and 55% (v/v) Results showed significant negative correlations between PFVI and groundwater levels (r = -0.173 to -0.889) and soil moisture (r = -0.835 to -0.808), indicating that lower groundwater levels and soil moisture increase fire risk. High PFVI values in July corresponded with the lowest rainfall (59 mm) and groundwater levels below 40 cm. The study highlights the importance of monitoring hydrometeorological conditions and soil properties to effectively predict and mitigate peatland fires. Our findings are crucial for developing strategies to manage peatland sustainability and reduce fire hazards, especially in tropical regions with prevalent oil palm cultivation.